2014
DOI: 10.1128/jb.01948-14
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Eukaryote-LikeO-GlcNAc Transferase of the Cyanobacterium Synechococcus elongatus PCC 7942 Hydrolyzes UDP-GlcNAc and Is Involved in Multiple Cellular Processes

Abstract: The posttranslational addition of a single O-linked ␤-N-acetylglucosamine (O-GlcNAc) to serine or threonine residues regulates numerous metazoan cellular processes. The enzyme responsible for this modification, O-GlcNAc transferase (OGT), is conserved among a wide variety of organisms and is critical for the viability of many eukaryotes. Although OGTs with domain structures similar to those of eukaryotic OGTs are predicted for many bacterial species, the cellular roles of these OGTs are unknown. We have identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
(51 reference statements)
0
15
1
Order By: Relevance
“…These data support a conserved role for O-GlcNAc protein modification in the generation of motile filaments in both hormogonium-forming and non-hormogonium-forming filamentous cyanobacteria. Although we do not provide biochemical evidence for O-GlcNAcylation activity of the putative OGT encoded by ogtA, such evidence has been reported for the OGT of Synechococcus elongatus PCC 7942 (seOGT) (23). Given that the catalytic GT41 domain of N. punctiforme OgtA (amino acids 374 to 729 of OgtA) shares 29% sequence identity with seOGT (NCBI BLASTP) and maintains conserved histidine and lysine residues (H280 and K445 of seOGT, corresponding to H386 and K554 of N. punctiforme OgtA) essential for seOGT function (23), it seems likely that ogtA encodes a functional OGT.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These data support a conserved role for O-GlcNAc protein modification in the generation of motile filaments in both hormogonium-forming and non-hormogonium-forming filamentous cyanobacteria. Although we do not provide biochemical evidence for O-GlcNAcylation activity of the putative OGT encoded by ogtA, such evidence has been reported for the OGT of Synechococcus elongatus PCC 7942 (seOGT) (23). Given that the catalytic GT41 domain of N. punctiforme OgtA (amino acids 374 to 729 of OgtA) shares 29% sequence identity with seOGT (NCBI BLASTP) and maintains conserved histidine and lysine residues (H280 and K445 of seOGT, corresponding to H386 and K554 of N. punctiforme OgtA) essential for seOGT function (23), it seems likely that ogtA encodes a functional OGT.…”
Section: Discussionmentioning
confidence: 81%
“…While structurally similar putative OGTs are also widespread among prokaryotes, their function is largely unknown (20)(21)(22). A recent study found that inactivation of a gene encoding a putative OGT in the cyanobacterium Synechococcus elongatus PCC 7942 resulted in a pleiotropic phenotype, and it provided biochemical evidence of OGT enzymatic activity for this gene product (23). Here, we provide a detailed characterization of the phenotype for an N. punctiforme ΔogtA mutant strain, the results of which implicate a role for O-GlcNAc protein modification in hormogonium development.…”
mentioning
confidence: 99%
“…To date, only a handful of prokaryotic OGTs have been identified, and the targets of these OGTs remain unclear ( Shen et al. 2006 ; Sokol and Olszewski 2015 ). Given the role OGTs play in eukaryotic posttranslational modification and the fact that many bacterial effector proteins show homology to eukaryotic proteins ( Galan 2009 ), it is possible that the presence of OGT in B. apis represents a pathway for host–microbe interaction and symbiont-mediated protein modification.…”
Section: Resultsmentioning
confidence: 99%
“…Several are secreted pathogenicity factors, like the NagJ from Clostridium perfringens ( 39 ) (hereafter Cp OGA), precluding a role in modulating intracellular O -GlcNAc signaling. A noteworthy exception is the recently identified OGT homologue found in the cyanobacterium Synechococcus elongates that appears to be involved in phosphorus retention within the cell, and genetic disruption causes the cells to aggregate ( 40 ). The underlying biological mechanisms of these phenotypes are not understood, and the organism lacks a predicted OGA homologue, precluding the existence of a dynamic O -GlcNAc proteome in this organism.…”
Section: Introductionmentioning
confidence: 99%